The Seismic Image of The Direct Hydrocarbon Indicators in Offshore Syria - Alsouki, Mohammad; Alali, Najeh; Alfaize, Mustafa M (Iraqi Journal of Science, 2020)
The easternmost Mediterranean Basin is a candidate to be one of the most important hydrocarbon regions in the world, especially after significant gas discoveries in Levantine Basin in 2009. Offshore Syria is one of the easternmost Mediterranean areas which is still an unexplored virgin area. The seismic interpretation results of the study area showed encouraging evidences of considerable hydrocarbon accumulations within different sedimentary successions, which are Direct Hydrocarbon Indicators (DHIs). Indicators such as reflectivity anomalies (flat spots and dim spots) and polarity reversal were found within significant structural highs of Tertiary or/Late Cretaceous and Early Jurassic successions. Also, gas chimney and a lot of bright spots were observed within a Plio-Pleistocene succession above tops and flanks of Messinian Salt diapirs and pinch-outs. The seismic attributes such as instantaneous frequency and phase and reflection strengths were used in this study to improve the seismic interpretation image in the gas-affected area, with the purpose of exhibiting strong amplitude abnormalities and confirming the occurrence of a polarity reversal and the low frequencies within and below some of the structural anticlines. These attributes suggest that there are potential hydrocarbon reservoirs.